Search and Pricing in Security Issues Markets: Theory and Evidence - Floros, Ioannis; Gatchev, Vladimir; Singh, Ajai; Wang, Qinghai (The Review of Corporate Finance Studies, 2025)
Abstract We present a search model that incorporates two key features of security issuances in centralized markets: the search for investors and information gathering. In the model, a seller contacts investors sequentially and uses reported interest to update the security’s value, while each investor reports interest strategically. We characterize the seller’s value-maximizing strategy in which search structure, duration, security pricing, and allocations are jointly determined. We derive novel implications from the model and find empirical support using a sample of accelerated seasoned equity offers, which have become prevalent in recent years and involve both search and information gathering.